A comparative analysis of wavelet-based coding algorithms in the H.264 framework - Asis, Juan Paolo R.
In this study, the performance of different wavelet-based algorithms in coding the residual frames of a video coder is examined and compared to the H.264 coding method. Three wavelet-based algorithms n Zerotree Coding (ZTC), Set Partitioning in Hierarchical Trees (SPIHT), and Significance-Linked Connected Component Analysis (SLCCA) n were implemented in MATLAB and inserted into an H.264-based video coder. The video coder uses H.264 variable block-size motion estimation and overlapped block motion compensation in getting the motion vectors and the residual frame. Adaptive arithmetic coding per residual frame was used in entropy coding. Objective tests show that the wavelet-based algorithms gives a comparable PSNR to that of an H.264 coder, ranging within 0.1 dB, and has around 20% less blocking in the range of 0.1 to 0.3 bits per pixel. Subjective tests show that viewers find the artifacts in the wavelet-coded videos less annoying than in the H.264 coded videos, scoring better by 0.5 on average on a scale from 0 to 10.